THE EFFECT OF TRAINING AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION AS AN INTERVENING VARIABLE - Moch. Ardiansyah Pramudya; Abdul Khodir Djaelani; Nur Hidayati (Pena Cendekia Insani, 2025)
This study examines the effect of training and work motivation on the performance of Café Nakoa Malang employees, with job satisfaction as a mediating variable. The study population consisted of 103 employees spread across four Café Nakoa branches, all of whom were sampled using saturation sampling techniques. The method used was a survey with data collection through questionnaires, which were then analysed quantitatively using SEM-PLS via the SmartPLS 4 software. The results showed that training and motivation had a positive and significant effect on performance, both directly and through job satisfaction. These findings underscore the importance of effective training and a fair motivation system in enhancing employee satisfaction and performance, particularly in the service industry with a self-service system. The research model was also proven to be valid and reliable, with significant relationships among the main variables.